Genes coding for sensitivity to interferon (IfRec) and soluble superoxide dismutase (SOD-1) are linked in mouse and man and map to mouse chromosome 16. - Cox, D R (1980)
By using 12 hamster-mouse hybrids segregating a mouse T(16;17)Bnr Robertsonian translocation chromosome in conjunction with 10 similar hybrids segregating normal mouse chromosomes, we have shown that the loci that control cellular sensitivity to interferon (IfRec) and code for the soluble enzyme superoxide dismutase (SOD-1) (superoxide:superoxide oxidoreductase; EC 1.15.1.1) are syntenic in the mouse and map to mouse chromosome 16. IfRec and SOD-1 are also syntenic in man. They have previously been assigned to the distal segment of the long arm of human chromosome 21, trisomy for which causes Down syndrome. Because both IfRec and SOD-1 map to mouse chromosome 16, it will now be possible to use mice trisomic for this chromosome to determine whether certain aspects of the Down syndrome phenotype in man are caused by an altered dosage of IfRec and SOD-1.